Stress circuitry: mechanisms behind nervous and immune system communication that influence behavior - Tong, Rose L.; Kahn, Ubaidah N.; Grafe, Laura A.; Hitti, Frederick L.; Fried, Nathan T.; Corbett, Brian F. (Frontiers in Psychiatry, 2023)
Inflammatory processes are increased by stress and contribute to the pathology of mood disorders. Stress is thought to primarily induce inflammation through peripheral and central noradrenergic neurotransmission. In healthy individuals, these pro-inflammatory effects are countered by glucocorticoid signaling, which is also activated by stress. In chronically stressed individuals, the anti-inflammatory effects of glucocorticoids are impaired, allowing pro-inflammatory effects to go unchecked. Mechanisms underlying this glucocorticoid resistance are well understood, but the precise circuits and molecular mechanisms by which stress increases inflammation are not as well known. In this narrative review, we summarize the mechanisms by which chronic stress increases inflammation and contributes to the onset and development of stress-related mood disorders. We focus on the neural substrates and molecular mechanisms, especially those regulated by noradrenergic signaling, that increase inflammatory processes in stressed individuals. We also discuss key knowledge gaps in our understanding of the communication between nervous and immune systems during stress and considerations for future therapeutic strategies. Here we highlight the mechanisms by which noradrenergic signaling contributes to inflammatory processes during stress and how this inflammation can contribute to the pathology of stress-related mood disorders. Understanding the mechanisms underlying crosstalk between the nervous and immune systems may lead to novel therapeutic strategies for mood disorders and/or provide important considerations for treating immune-related diseases in individuals suffering from stress-related disorders.